Uji Kesesuaian Kinerja Generator dan Tabung Sinar-X pada MSCT Philips 128 Slice di Instalasi Radiologi, Rumah Sakit Daerah Mangusada - Ramadan Purnama, Muhammad Mada; Sutapa, Gusti Ngurah; Pranditayana, I Nyoman (Universitas Hamzanwadi, 2023)
This research aimed to determine the Compliance test of MSCT Philips 128 Slice generator and X-ray tube performance at Mangusada Hospital in accordance with the tolerance limits based on the BAPETEN Head Regulation of the Republic Indonesia Number 2 of 2022 so that it can be stated that the generator and X-ray performance is in reliable condition. In this research, Raysafe Xi CT and Raysafe Xi R/F were used to measure the output value of radiation dose, tube voltage and HVL thickness on MSCT Philips 128 Slice by carrying out four test activities, namely radiation output reproducibility test, radiation output linearity test, test, and X-ray beam quality test. The performance test of the generator and X-ray tube has been carried out on MSCT Philips 128 Slice with obtained Coefficient of Variation (CV) value in the radiation output reproducibility test of 0.00278, Coefficient of Linearity (CL) value in the radiation output linearity test of 0.00882, at a tube voltage of 80 kVp is 6.30280 mGy/100mAs, at a tube voltage of 120 kVp is 19.59800 mGy/100mAs, at a tube voltage of 130 kVp is 24.48431 mGy/100mAs, and the HVL thickness at a tube voltage of 120 kVp is 8.79 mmAl. This result show that the performance MSCT Philips 128 Slice generator and X-ray tube in reliable condition.